NILAI-NILAI KARAKTER DALAM PERMAINAN TRADISIONAL - Nadziroh Nadziroh; Chairiyah Chairiyah; Wachid Pratomo (Universitas Sarjanawiyata Tamansiswa, 2019)
The purpose of writing this article is to examine values in traditional games. Value is the weight or quality of good deeds contained in various things that are considered valuable, useful, and has benefits. From the results of the study, it can be concluded that there are character values in traditional games. These values include the values of discipline, dexterity, social, health, honesty, sportsmanship, cooperation, and hard work.